2022
DOI: 10.3389/fphar.2022.966348
|View full text |Cite
|
Sign up to set email alerts
|

Alpiniae oxyphyllae fructus possesses neuroprotective effects on H2O2 stimulated PC12 cells via regulation of the PI3K/Akt signaling Pathway

Abstract: Backgroud: Alzheimer’s disease (AD) is a typical neurodegenerative disease, which occurs in the elderly population. Alpiniae oxyphyllae Fructus (AOF) is a traditional Chinese medicine that has potential therapeutic effect on AD, but the mechanism behind it is unclear.Methods: Firstly, the main chemical components of AOF were identified by LC-MS, while the main active ingredients and targets were screened by TCMSP database. At the same time, AD-related target proteins were obtained using Genecards and OMIM data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The results showed that dietary AOP supplemented with 3 g/kg decreased the concentration of Caspase 8 in serum, decreased the expression of Bax and Caspase3, and increased the ratio of Bcl-2/Bax in ovary. Research indicated that Alpiniae oxyphyllae Fructus ( AOF ) decreased H 2 O 2 -induced damage to PC12 cells by upregulating Bcl-2 expression and downregulating Bax and caspase-3 expression in PC12 cells ( Li et al, 2022 ). Based on these findings, it's plausible that AOP might modulate apoptosis in laying breeder hens.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that dietary AOP supplemented with 3 g/kg decreased the concentration of Caspase 8 in serum, decreased the expression of Bax and Caspase3, and increased the ratio of Bcl-2/Bax in ovary. Research indicated that Alpiniae oxyphyllae Fructus ( AOF ) decreased H 2 O 2 -induced damage to PC12 cells by upregulating Bcl-2 expression and downregulating Bax and caspase-3 expression in PC12 cells ( Li et al, 2022 ). Based on these findings, it's plausible that AOP might modulate apoptosis in laying breeder hens.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that an LRP-1 agonistic peptide, SP16, which inhibits ROS production, prevented NAFLD-induced depletion of CD4 + T cells in the liver and spleen [ 19 , 20 , 21 ]. However, such restoration of CD4 + T cells, without modulating the inflammatory immunological patterns in the liver, was not sufficient to overcome HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Has a long history of application in traditional clinical Chinese medicine ( Yang et al, 2020 ). In traditional medicine, AOF has been widely utilized for treatment of emesis, diarrhea, frequent urination, spermatorrhea and so on ( Li R. et al, 2022 ). Modern pharmacological research manifested that AOF had anti-oxidant ( Bian et al, 2013 ), anti-inflammatory ( Qi et al, 2019 ), neuroprotective ( Liu et al, 2020 ), anti-AD ( Bian et al, 2021 ), and other effects.…”
Section: Introductionmentioning
confidence: 99%